Performance analysis of a nonlinear full vehicle model using double-lane change maneuver: a comparison with CarSim - Ruslan, Ilyanie; Abd Kadir, Zulkiffli; Amer, Noor Hafizah; Mohd Nor, Elya (UiTM Press, 2026)
Vehicle modelling and verification are fundamental components of the modern automotive development process, enabling researchers to optimize controller designs and ensure safety before actual testing. By employing simulation techniques, researchers can accurately predict vehicle performance and behaviour under a wide range of driving conditions. This study focuses on the development and verification of a seven-degree-of-freedom (7-DOF) full vehicle dynamics model developed to simulate real vehicle responses. The developed model consists of a handling system model, tyre dynamics model, load distribution, and individual wheel dynamics, including functions for tyre slip ratio and slip angle. The model is driven by two inputs, namely steering wheel angle and throttle position. To verify the model, its responses are compared to those generated by the CarSim software under similar vehicle parameters and driving conditions involving a double lane change maneuver at a speed of 120 km/h. The results show that the model closely follows the dynamic behaviours obtained from CarSim. The percentage difference of Root Mean Square (RMS) between the developed model and the CarSim analysis is used to evaluate the accuracy of the model. Based on the RMS values at 120 km/h, the maximum error occurred in longitudinal acceleration with a percentage difference of 5.63%. Overall, the verification results indicate that the developed model effectively tracks CarSim outputs within an acceptable range of error, demonstrating its potential for representing vehicle system dynamics under various driving conditions.